SNP analysis of ITS1-5.8S-ITS2 rDNA loci in modern and ancient melons (Cucumis melo) - Szabó, Zoltán; Gyulai, Gábor; Tóth, Zoltán; Heszky, László (Acta Agraria Debreceniensis, 2007)
ITS (internal tanscribed spacer) profiles of the aDNA (ancient DNA) of seed remains extracted from an extinct sample recovered from the 15th century (Budapest, Hungary) were compared to 31 modern melon cultivars and landraces. An aseptic incubation followed by ITS analysis was used to exclude the exogenously and endogenously contaminated (Aspergillus) medieval seeds and to detect SNPs in ITS1-5.8S-ITS2 region of rDNA (ribosomal DNA). SNPs were observed at the 94–95 bp (GC to either RC, RS or AG) of ITS1; and at 414 bp (A-to-T substitution), 470 bp (T to Y or C), 610 bp (A to R or G) of ITS2. The results facilitate the final aim of molecular and morphological reconstructions of ancient melon tpyes.